2020
DOI: 10.1038/s41598-020-76332-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary surfactant inhibition of nanoparticle uptake by alveolar epithelial cells

Abstract: Pulmonary surfactant forms a sub-micrometer thick fluid layer that covers the surface of alveolar lumen and inhaled nanoparticles therefore come in to contact with surfactant prior to any interaction with epithelial cells. We investigate the role of the surfactant as a protective physical barrier by modeling the interactions using silica-Curosurf-alveolar epithelial cell system in vitro. Electron microscopy displays that the vesicles are preserved in the presence of nanoparticles while nanoparticle-lipid inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Different studies have demonstrated that surfactant components interact with nanoparticles. These interactions can determine the lifetime, fate, and toxicity of the nanomaterial in the airways [9,37] as well as adversely affect pulmonary surfactant function [6]. Therefore, in this work, we evaluated whether PHA nanoparticles are suitable for lung drug delivery by studying the interaction of this nanomaterial with pulmonary surfactant and interfacial films made of the main surfactant lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have demonstrated that surfactant components interact with nanoparticles. These interactions can determine the lifetime, fate, and toxicity of the nanomaterial in the airways [9,37] as well as adversely affect pulmonary surfactant function [6]. Therefore, in this work, we evaluated whether PHA nanoparticles are suitable for lung drug delivery by studying the interaction of this nanomaterial with pulmonary surfactant and interfacial films made of the main surfactant lipids.…”
Section: Discussionmentioning
confidence: 99%
“…[6]). On the other hand, the formation of the corona alters the surface properties of the nanoparticles and, therefore, can modify their biodistribution and toxicity [8,9]. For instance, the coating of nanoparticulated gels with a lipoprotein film that contains SP-B favors the vehiculization of encapsulated small interfering RNA [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, if AgNPs avoid deposition by the conciliary escalator, they will reach the alveoli, where a protective 0.2-5 µM layer of pulmonary surfactant can bind to the AgNPs' surface by corona formation processes leading to excretion, ingestion, or translocation. The fluid secreted by type II cells is composed of lipids and hydrophobic surfactant proteins [119]. The last line of defense contains type I and II pneumocytes monolayer in the epithelial tissue of the alveoli and a group of heterogeneous macrophages distributed on the respiratory surface.…”
Section: Nanotoxicity Models To Evaluate Lung Cytotoxicitymentioning
confidence: 99%
“…[ 40 ] In the alveolar epithelium, pulmonary surfactant presents a barrier to NP uptake. [ 41 ] The pulmonary surfactant is composed of 92% lipids (consisting predominantly of zwitterionic and dipalmitoylphosphatidylcholines) and protein [ 42 ] and forms a 0.2–0.5 µm thick layer on the surface of epithelium cells. The proteins, notably surfactant proteins SP‐A and SP‐D, can mediate interactions with immune cells and facilitate phagocytosis presenting a barrier that can be avoided or exploited to achieve effective drug delivery.…”
Section: Single Cell Levelmentioning
confidence: 99%